2021
DOI: 10.1002/er.7454
|View full text |Cite
|
Sign up to set email alerts
|

Operating performance of multi‐modular water‐phase change material tanks for emergency cooling in an underground shelter

Abstract: Summary Latent heat thermal energy storage can not only alleviate the mismatch between supply and demand but also improve the performance and dependability of the energy system. Unfortunately, previous research achieves a specific engineering load shifting using a single water‐phase change material (PCM) tank, the volume of which is tailored to the specific cooling or heating load. This paper proposes the concept of multi‐modular water‐PCM tanks (MMWPT), which offer flexibility and are simple to be mass‐produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…• Step 3: Prior research has focused on achieving a specified load shifting through a single water-PCM tank, with its volume tailored to meet the necessary cooling or heating load. Zeng et al's 57 proposal for thermal storage in the underground shelter's emergency mode also includes MMWPT, which offers flexibility and is simple to mass-produce. The PCM is first kept in a solid form by geothermal energy, and the tank is naturally cooled after the PCM has melted.…”
Section: Utilization Of Latent Heat Thermal Energy Storage (Lhtes) In...mentioning
confidence: 99%
See 1 more Smart Citation
“…• Step 3: Prior research has focused on achieving a specified load shifting through a single water-PCM tank, with its volume tailored to meet the necessary cooling or heating load. Zeng et al's 57 proposal for thermal storage in the underground shelter's emergency mode also includes MMWPT, which offers flexibility and is simple to mass-produce. The PCM is first kept in a solid form by geothermal energy, and the tank is naturally cooled after the PCM has melted.…”
Section: Utilization Of Latent Heat Thermal Energy Storage (Lhtes) In...mentioning
confidence: 99%
“…The phase change plates are spaced 20 mm apart. Step 3: Prior research has focused on achieving a specified load shifting through a single water‐PCM tank, with its volume tailored to meet the necessary cooling or heating load. Zeng et al's 57 proposal for thermal storage in the underground shelter's emergency mode also includes MMWPT, which offers flexibility and is simple to mass‐produce. The PCM is first kept in a solid form by geothermal energy, and the tank is naturally cooled after the PCM has melted. Step 4: The geothermal heat pump system (GHPS) is connected in series with MMWPT to provide cooling for the underground shelter in regular and emergency modes, respectively.…”
Section: Case Studiesmentioning
confidence: 99%
“…Often, the local PCM temperatures are used to validate numerical results with experimental measurements (e.g., [65,98,104,122,129,130]). In contrast, experimental studies are limited to discrete sensor locations (e.g., [63,64,69,72,83,[87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][108][109][110][111][112][113][114][115][116][117][118]) or global liquid fraction techniques (e.g., [87,101]).…”
Section: State Indicatorsmentioning
confidence: 99%
“…In numerical studies reporting internal energy as a function of time is commonly done although most studies report latent stored internal energy (e.g., [71,99,104,130]) or total liquid fraction (e.g., [65, 66, 68, 70, 71, 75, 77, 93, 99, 102, 104, 106, 109, 111, 113, 115, 120-122, 124-128, 130-132, 134, 136]) instead of total stored energy (e.g., [75,111,115,134,137,138]). In experimental studies, the total liquid fraction is sometimes reported (e.g., [67,87,101]) however local temperature measurements are far more commonly reported (e.g., [63,64,69,72,76,83,[87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][105][106][107][108][109][110][111][112][113]…”
Section: State Indicatorsmentioning
confidence: 99%